Oral dydrogesterone as an adjunctive therapy in the management of preterm labor: a randomized, double blinded, placebo‐controlled trial - Suparudeewan Thongchan; Vorapong Phupong (BMC, 2021)
Abstract Background Preterm birth is a major challenge in obstetric and perinatal care. It is the leading cause of neonatal death. The primary aim of this study was to evaluate the efficacy of oral dydrogesterone on latency period in managing preterm labor. The secondary aims were to evaluate the gestational age at delivery, percentage of preterm delivery before 34 weeks and 37 weeks, time to recurrent uterine contraction, pregnancy outcomes, neonatal outcomes, compliance and side effects. Methods This was a randomized, double blinded, placebo-controlled trial. Forty-eight pregnant women with preterm labor, singleton pregnancy, and gestational age of 24-34 weeks were enrolled into the study. The study group received 10 mg of oral dydrogesterone three times per day and the control group received placebo. All pregnant women received standard treatment with tocolytic and antenatal corticosteroids. Results The median latency periods were not significantly different between the dydrogesterone group (27.5 days) and placebo group (34 days, p = 0.45). Additionally, there were no differences in the gestational age at delivery, percentage of preterm delivery before 34 weeks and 37 weeks, pregnancy outcomes, neonatal outcomes, compliance and side effects. However, the time to the recurrence of uterine contractions in participants that had recurrent preterm labor was longer in the dydrogesterone group than in the placebo group (30.6 ± 12.3 vs 13.7 ± 5.0 days, p = 0.01). Conclusions Adjunctive treatment with 30 mg of oral dydrogesterone could not prolong latency period in preterm labor when compared to placebo. Trial registration ClinicalTrials.gov (Clinical trials registration: NCT 03935152 , registered on May 2,2019).